Pansamantala - Singh, Joey Alexis E. 1993- (Quezon City College of Mass Communication, University of the Philippines Diliman, 2016)
"Between the unborn child she carries in her womb and the impermanent job she longs to secure, Ofi deeply struggles to keep her premature family afloat. Her impending regularization at a grocery store where she works is tainted by a choice to join her other half for what seem like a good opportunity abroad. Her determination is also put to the test when she finds herself helping someone to help in return, until she realizes that what's at stake is also her morality. The film explores the Marxist Perspective on Family in which a family functions as society's basic unit to serve the needs of Capitalism. In the film, Ofi, along with the other characters belonging to the working class, strives to attain the Filipino dream for "maginhawang buhay". Despite the excessive consumption of work hours and its demands, the characters only receive what is substantial. They are all confined by labor contractualization, wherein nothing is permanent, not even the concept of family of life. The film is also guided by Feminist Theory exploring the gender equality in labor."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman